â€œSEMAMPAIâ€ SEHAT, MANAJERIAL, MANDIRI, DAN PANDAI: KKN-PPM, MUARA ANCALONG, KUTAI TIMUR - Nugroho, Rudy Agung; Sanjaya, Ari Susandy; Ramdan, Iwan Muhammad; Rudianto, Rudianto; Prahastika, Widha (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community Development Program-learning and community service program or Kuliah kerja nyata-pembelajaran dan pengabdian kepada masyarakat (KKN-PPM) which is a form of community service has been done from July-August 2019 in the Kelinjau Ulu and Kelinjau Ilir village, Muara Ancalong, East Kutai, East Kalimantan. The purpose of the KKN-PPM was to empower the community to be more productive. The theme of the KKN-PPM programÂ  was "Semampai" which has a meaning sehat (healthy), manajerial (managerial), mandiri (independent) and pandai (smart). The KKN-PPM was performed by 20 undergraduate students from various faculties and under supervised by field supervisors. In addition to these thematic activities and KKN-PPM program, each undergraduate student also performed individual programs which related to their scientific background. In conclusion, the KKN-PPM is useful to the community in Kelinjau ulu and ilir to enhance the productivity, to be healthier, actively reading and smarter and more insightful.